Kultivasi Mikroalga Chlorella Sp. Secara Fed-Batch Dalam Media POME Sebagai Bahan Baku Bioetanol - Dina Citra Naomi Harianja; Sri Rezeki Muria; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bioethanol is an environmental friendly biofuel, one of the raw materials is microalgae, because microalgae can produce carbohydrates which can be used for fermentation in the process of bioethanol production. In this research the microalgae Chlorella sp. cultivated in the palm oil waste media (POME) in a fed-batch culture. The purpose of this researchare study the effect of fed POME media in fed-batch culture on the growth of Chlorella sp., to calculate the specific growth rate of Chlorella sp. microalgae, determine the effect of fed-batch processes on the reduction of POME COD and carbohydrate content of Chlorella sp. Microalgae Chlorella sp. 600 ml with 4.8 x 106 cell density were cultivated for 12 days using bioreactors with addition of waste variations 0.45 L / day, 0.9 L / 2 days and 1.35 L / 3 days, and batch process with addition of 5.4 wastes L. POME COD analysis is carried out at the beginning and end of cultivation, cell density and carbohydrate calculation is performed at each waste addition. The best results were obtained with variations in the addition of POME 0.9 L every 2 days, POME COD of 750 mg / L, and density cel 4.432 x 106 with carbohydrates 190,51 mg / L. Keywords : Chlorella sp., fed-batch cultivation, POME, carbohydrate.